The influence of general practitioner and patient sex on the treatment of major depression - Elisabeth Jufresa-Blanch; Elisabeth Jufresa-Blanch; Neus Carrilero; Neus Carrilero; Neus Carrilero; Anna García-Altés; Anna García-Altés; Anna García-Altés (Frontiers Media S.A., 2023)
Introduction: Biological and sociocultural factors may lead to a significant gender bias in the treatment of major depression and thus contribute to accentuating gender inequalities. However, the influence of the general practitioner's (GP's) sex on the prescription of antidepressants has not been adequately assessed in previous work and remains unclear. This retrospective cohort study aims to determine the influence of GP and patient sex on the treatment of major depression.Methods: The study population comprised 87,629 patients (33.56% male patients and 66.44% female patients) aged over 15 years newly diagnosed with major depression recorded between 2017 and 2019 in Catalonia, Spain. Logistic regression models were used to evaluate the effect of GP sex on the therapeutic strategy (i.e., whether antidepressants were prescribed at the first diagnostic visit). Cox proportional hazards models and survival analyses were conducted to compare, according to GP and patient sex, the probability that a patient would be prescribed an antidepressant at any time during the study period. Finally, a multiple linear regression analysis was performed to assess the pharmacological intensity of the treatment [monthly fluoxetine-equivalent defined daily dose (DDD)].Results: Female patients were more likely to be prescribed an antidepressant at the time of diagnosis, both by male [OR = 1.11, 95% CI = (1.05, 1.17), p<0.001] and female GPs [OR = 1.13, 95% CI = (1.09, 1.17), p<0.001]. Similarly, female patients were 8% and 9% more likely than male patients to be prescribed an antidepressant from male [HR = 1.08, 95% CI = (1.05, 1.11), p<0.001] and female GPs [HR = 1.09, 95% CI = (0.92, 1.07), p<0.001], respectively, during the study period. Female GPs prescribed less antidepressants than male GPs: an average of 0.39 less monthly fluoxetine-equivalent DDD [β = −0.39, 95% CI = (0.10, −3.92), p<0.001].Discussion: Few differences are observed between male and female GPs regarding the therapeutic strategy and its intensity for the treatment of major depression. However, both male and female GPs are influenced by biases and stereotypes that entail differential antidepressant-prescribing behaviors in accordance with the sex of the patient and their characteristics.